1987
DOI: 10.1152/ajpendo.1987.253.1.e40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasting on serum lactogenic hormone concentrations during mid- and late pregnancy in mice

Abstract: Hormonal and metabolic responses to fasting were studied in pregnant Swiss Webster mice. Food was removed from pregnant mice 12, 24, 36, or 48 h before death on day 12 or 15 of pregnancy. Serum mouse placental lactogen-II (mPL-II), mouse growth hormone (mGH), mouse prolactin (mPRL), free fatty acids (FFA), and glucose concentrations were determined for each group. In comparing fasted animals with fed controls, there was a significant increase in the serum mPL-II concentration after 24 and 48 h of fasting on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…The FFA turnover experiments corroborate this finding, as FFA concentration was not different from 4 to 16 hours of fasting. Others have found similar data showing no change in FFA concentration in mice from 4 to 16 [14] and from 12 to 48 hours of fasting [15][16][17][18]. We extend this finding to suggest both control and MCKhLPL mice reach a plateau in fasting FFA concentration within 1 to 2 hours of fasting.…”
Section: Ffa Concentrationsupporting
confidence: 87%
See 1 more Smart Citation
“…The FFA turnover experiments corroborate this finding, as FFA concentration was not different from 4 to 16 hours of fasting. Others have found similar data showing no change in FFA concentration in mice from 4 to 16 [14] and from 12 to 48 hours of fasting [15][16][17][18]. We extend this finding to suggest both control and MCKhLPL mice reach a plateau in fasting FFA concentration within 1 to 2 hours of fasting.…”
Section: Ffa Concentrationsupporting
confidence: 87%
“…There are no data in the literature comparing FFA concentration in MCKhLPL and control mice during a longer fast. Considering the plateau in FFA concentration observed in this and other studies after a prolonged fast [15][16][17][18], we expected to find unchanged FFA concentration from 4 to 16 hours of fasting in both transgenic and control mice. These data support the finding that within 2 hours of fasting in mice, FFA concentration increases to a level that does not change for up to 24 hours.…”
Section: Ffa Concentrationmentioning
confidence: 46%
“…GLP-1 has been shown to increase expression of the Pancreas duodenal homeobox 1 (Pdx-1) gene, thereby stimulating ß-cell proliferation [14]. However, Pdx-1 levels are not increased by PRL [25], which plays important roles in ß-cell proliferation during pregnancy [4], [9], [10], [11]. Several studies indicate that signaling pathways for PRL and those for GLP-1 are independent [19], [26] [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that prolactin (PRL), placental lactogens (PLs), and serotonin play important roles in the pregnancy-associated changes in ß-cell mass and function in rodents [4], [9], [10], [11]. On the other hand, involvement of glucagon-like peptide-1 (GLP-1) in the pregnancy-associated changes in ß-cell mass and function has not been investigated, although it is well established that GLP-1 supports β-cell proliferation and inhibits apoptosis of these cells [12], [13], [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…These include the pituitary gland (10,11), GH (12), the ovaries (13), progesterone (13,14), genotype (15), maternal nutritional status (16), and litter size (8,15). Little is known about the role of growth factors in regulating mPL secretion.…”
mentioning
confidence: 99%